¿Quién conforma la comunidad de la TEI en español? Análisis de los datos de una encuesta - Gimena del Rio Riande; Susanna Allés-Torrent (Journal of the Text Encoding Initiative)
In this article we analyze the results obtained in a survey on the use of the Text Encoding Initiative for Digital Humanities projects in Spanish that was conducted in early 2022 within the project “Communicating the Text Encoding Initiative to a Multilingual User Community” funded by the A. Mellon Foundation. The main objectives of our analysis are to understand who conforms the TEI user community in the Spanish-speaking world or in Spanish text-related initiatives, what types of TEI-related academic training is offered today, how and for what purposes this type of text encoding is used, and what are the existing resources for teaching and learning.